Service-Oriented Architecture for E-Marketplace Model: A Study Based on Multi-Platform Distributed System - Yaddarabullah; Muttaqin, M. F.; Rafiansyah, M. (An Overview on Business, Management and Economics Research Vol. 2, 2023)
The goal of this work is to examine and create an electronic marketplace architecture that allows for the distribution of data with online payment and courier services while integrating items from different electronic commerce. E-commerce (electronic commerce) is the activity of electronically buying or selling of products on online services or over the Internet. E-commerce draws on technologies such as mobile commerce, electronic funds transfer, supply chain management, Internet marketing, online transaction processing, electronic data interchange (EDI), inventory management systems, and automated data collection systems. E-commerce is in turn driven by the technological advances of the semiconductor industry, and is the largest sector of the electronics industry. Online transactions now have a solution thanks to e-commerce. According to information from Indonesia's Central Bureau of Statistics, there were 26.2 million users in 2016 and that number increased by 17% between 2006 and 2016. On the other side, Indonesia has seen a tremendous increase in the growth of e-marketplace. In 2018, there were 100 trillion transactions. E-commerce players are now still unable to rival the e-marketplace as it stands. This is a result of e-commerce's restricted supply and product selection. Increasing the number of clients and transactions is one of the issues e-commerce managers encounter. The multi-platform e-marketplace model was developed that was integrated and could distribute products from several e-commerce. Service oriented architecture was used as a method in integrating and distributing products from e-commerce to e-marketplace. Based on the results of testing with 90 request can be concluded that the process of data distribution from e-commerce to e-marketplace can be done in a fast time with average loaded time of 0,72 seconds and the size of data accessed is relatively small with packed average size of 5,68 KB. The conclusion of this study remains the use of service-oriented architecture can be applied for e-marketplace that integrated with several e-commerce for supporting some feature like online payment and courier.